Comparison between atrial fibrillation-triggered implantable cardioverter-defibrillator (ICD) shocks and inappropriate shocks caused by lead failure: different impact on prognosis in clinical practice - Kleemann, Thomas; Hochadel, Matthias; Strauß, Margit (Journal of cardiovascular electrophysiology, 2012)
Prognostic Impact of Inappropriate Shocks. Introduction: Recent studies suggest a worse impact of inappropriate shock therapies on the outcome of patients with an implantable cardioverter-defibrillator (ICD). However, it is not known whether the worse impact is attributed to the ICD shock itself or due to the underlying heart disease. The aim of the study was to evaluate the impact of inappropriate ICD shocks on clinical outcome by comparing ICD shocks triggered by atrial fibrillation (AF) with shocks caused by lead failure. Methods and Results: A total of 1,411 consecutive patients of the prospective single-center ICD-registry Ludwigshafen who underwent an ICD implantation between 1992 and 2008 for primary or secondary prevention of sudden cardiac death were analyzed. During the median follow-up of 3 years, 297 (21%) patients experienced inappropriate ICD shocks. Sixty percent of patients had inappropriate shocks due to AF and 24% due to lead defect or T-wave oversensing. Multiple ICD shocks (≥2) triggered by AF were associated with a worse prognosis, whereas a single shock due to AF or 1 or multiple shocks resulting from lead failure were not. ICD shocks caused by AF occurred more often in tandem with a serious adverse event than in patients with a lead failure (15% vs 6%, P < 0.05). Conclusion: Multiple ICD shocks triggered by AF are associated with a worse prognosis in ICD patients, whereas a single shock due to AF or shocks resulting from lead failure are not. These data support that the ICD shock itself has no worse impact on the outcome of ICD patients. (J Cardiovasc Electrophysiol, Vol. 23, pp. 735-740, July 2012)